Uttar Pradesh Government uses CCAFS novel research on underground solutions for Irrigation to develop district water development plans (US$1.2 million) - CGIAR Research Program on Climate Change, Agriculture and Food Security (2017)
Government of Uttar Pradesh has developed district development plans using our research on this novel new ‘underground’ solution (UTFI) that transforms water hazards into opportunities and provides a new tool for CSA. The Plans have been finalized with District Rural Development Agency of Rampur District (pop. 2million), with an budget allocation of US$1.2million. District officials are being provided with training and others forms of support to ensure upscaling proceeds successfully. Interest has been expressed by other districts in Uttar Pradesh.